2005
DOI: 10.1002/art.20987
|View full text |Cite
|
Sign up to set email alerts
|

An opposing time‐dependent immune‐modulating effect of the sympathetic nervous system conferred by altering the cytokine profile in the local lymph nodes and spleen of mice with type II collagen–induced arthritis

Abstract: Objective. The sympathetic nervous system (SNS) seems to play a proinflammatory role in the early asymptomatic phase of arthritis, but its role in the late stages of chronic arthritis is not well known. The purpose of this study was to examine the effects of the SNS on late-stage chronic arthritis in mice with type II collagen-induced arthritis (CIA).Methods. We tested the effects of the SNS by ablating sympathetic nerves at different time points in mice with CIA. Early sympathectomy was performed 7 days befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
141
1
8

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 145 publications
(161 citation statements)
references
References 31 publications
11
141
1
8
Order By: Relevance
“…Second, we were unable to identify a particular nerve quality required for K/BxN serum-transferred arthritis. This finding contrasts with previous reports of an effect of manipulating the SNS in other mouse models of inflammatory arthritis (sometimes via the same inhibitors) (3,15). A likely explanation for the divergent results is that the models previously interrogated are rather different: Unlike the K/BxN serum-transfer system, they encompass both the initiation and effector stages of arthritis and depend on the injection of an adjuvant to induce disease.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Second, we were unable to identify a particular nerve quality required for K/BxN serum-transferred arthritis. This finding contrasts with previous reports of an effect of manipulating the SNS in other mouse models of inflammatory arthritis (sometimes via the same inhibitors) (3,15). A likely explanation for the divergent results is that the models previously interrogated are rather different: Unlike the K/BxN serum-transfer system, they encompass both the initiation and effector stages of arthritis and depend on the injection of an adjuvant to induce disease.…”
Section: Discussioncontrasting
confidence: 72%
“…The SNS seems to exert pro-or anti-inflammatory activity depending on the context, typically promoting inflammation at the outset of an immune response and reining it in at later stages (14). For example, blockade of β2 sympathetic signaling delayed the onset of antigen-induced arthritis and reduced its severity (3), whereas sympathectomy performed late in the course of collagen-induced arthritis worsened disease manifestations (15). To test the influence of the SNS in the K/BxN serum-transfer system, we administered, along with the serum, a set of pharmacologic agents that operate by a diversity of mechanisms.…”
Section: Assessment Of the Contribution Of Diverse Nerve Types To K/bxnmentioning
confidence: 99%
“…Thus, CII-induced arthritis in DA rats appears to be a suitable model with which to analyze the mechanisms that interfere with the activation of the HPA axis during arthritis, a defect that is not observed during other experimentally induced inflammatory/autoimmune diseases, such as experimental autoimmune encephalomyelitis (28,32,33). Furthermore, it has been shown that the density of noradrenergic nerve fibers is reduced in the inflamed joints of RA patients (34) and in mice with CII-induced arthritis (2), and this finding was confirmed in our studies of the rat model. Sympathetic denervation could be related to local activation of immune cells, since we have reported a similar reduction in the density of noradrenergic fibers in lymphoid organs of mice in which an autoimmune/lymphoproliferative disease develops spontaneously (35).…”
Section: Discussionmentioning
confidence: 99%
“…Cryosections were immunostained with primary antibodies against tyrosine hydroxylase (Chemicon, Temecula, CA), the key enzyme of NA synthesis in sympathetic nerve endings, according to the protocol described elsewhere (7). The numbers of stained nerve fibers with a minimum length of 50 m (indicated by a small-micrometer eyepiece) were counted in selected fields at 400ϫ magnification, as recently described (2). At least 4 rats were examined at each time point.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation